Adult Congenital Permanent Bilateral Dislocation of the Patella with Full Knee Function: Case Report and Literature Review - Alessandro Bistolfi; Giuseppe Massazza; David Backstein; Stefano Ventura; Raul Cerlon; Maurizio Crova (Case Reports in Medicine)
Congenital permanent dislocation of the patella is a rare disorder of the knee joint in which the patella is permanently displaced, even in extension and is fixed on the lateral aspect of the femoral condyle. The dislocation is irreducible without surgical techniques. This rare condition is usually detected within the first decade of life, because of inability of active extension in the knee and impaired ability during walking. This report presents an unusual case of a 51-year-old man with bilateral congenital permanent dislocation of the patella. The pathology had never been treated because there were few symptoms. The patient presented with right knee pain caused by a fall on the knee during his work. The right knee was painful on the lateral side and the clinical signs were positive for pathology of the lateral meniscus, confirmed by MRI. The clinical and the imaging findings suggested a lesion of the lateral meniscus as the probable cause of the pain. Therefore we performed a knee arthroscopy, whose intra-operative findings confirmed the MRI findings. During the surgery we performed just a selective arthroscopic meniscectomy, without correcting patella dislocation, because the condition was unusually asymptomatic before the trauma.